Effect on performance audit implementation of good corporate governance in kab.Luwu (Case Study Inspectorate Kab.Luwu) - Rahmawati A. (Journal of Economics and Behavioral Studies, 2015)
This paper describes how internal audit can support Good Corporate Governance in local government. How auditor capability and quantity can be accepted by 33 department of the local government Luwu. It also finds that Auditor capacity to do audit with independency, professionalisms and quality of auditor. This paper elaborates that the internal audit such as finance audit, compliance audit, and operational audit is required in local government to decrease fraud before the external audit find, and can be good for corporate governance. One of the things that can realize good corporate governance is seen from the performance of any organization of government activities, good performance in terms of achieving policy objectives, regulations and applicable law, the achievement of performance in an efficient, effective, and economical, as well as the compatibility between the performance achieved with established criteria. To assess the extent to which the achievement of local government performance in serving the interests of society, it is necessary to audit the performance. The purpose of this study was to determine the effect of Internal Audit on the implementation of good corporate governance in local government Luwu. The sample in this study was all local governments Internal Auditor in Luwu district Inspectorate office. The collection of information is done by compiling a list of questions that are appropriate for the respondents submitted to the analysis method used in this research is quantitative method by using a simple linear regression analysis were processed with SPSS software version 18. The results of this study concluded that the existence of an internal audit will encourage the achievement of implementation of good corporate governance system within the Inspectorate so that later in outline will encourage financial governance system within the district will go well. Although many other factors that will support that have not been investigated as thoroughly as the auditor's own characteristics, auditor ethics deal other factors. Accountability and transparency have become important issues in the management of an organization that disclosure with full disclosure will provide a thorough understanding of users of financial statements. Compliance audit of internal audit affects the implementation of good corporate governance can be seen that the results of testing for compliance audits variable has a probability of 0.041 significance where the value is less than 0.05. Thus H4 accepted, this means that the compliance audit of internal audit significantly influence the implementation of good corporate governance in Luwu.